Pengaruh Tingkat Investasi, Nilai Tukar Rupiah dan Pertumbuhan Ekonomi terhadap Tingkat Pengangguran - Made Santana Putra Adiyadnya; Ni Nyoman Adityarini Abiyoga Vena Swara (UNHI Press, 2021)
Economic development is a process increase in real income of the population in a country as sustainably. Macroeconomy growth becomes one of the indicators for rate economic conditions in a country. Unemployment in the macroeconomy is a complicated problem from human resources in each country, including Indonesia. Bali province is one of the provinces that have a very tight population, so there are many workers and unemployment. The purpose of this study are to know the effect of economic growth, inflation and investation partially to open unemployment rate of Bali Province and to know the effect of economic growth, inflation and investation simultaneously to open unemployment rate of Bali Province. The result of this research are economic growth variable partially has a negative and significant effect on to open unemployment rate of Bali Province, while the inflation variable partially has an insignificant effect on to open unemployment rate of Bali Province, and investation variable partially has a positive and significant effect to open unemployment rate of Bali Province. The last one, that economic growth, inflation, and investation simultaneously have a significant effect to open unemployment rate of Bali Province.